2003
DOI: 10.1097/01.smj.0000047627.78898.ab
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Efforts Improve Compliance with Acute Stroke Guidelines

Abstract: Feedback on performance, coupled with proactive collaboration with emergency department staff, resulted in improved compliance with the stroke guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…They can involve the derivation of quality indicators and the aggregation of expert opinions as well as various clinical data to obtain compliance scores [37,38]. We did not incorporate such checks into this study, but think that integration of various such metrics would be possible with the same set-up, yielding valuable insights for decision makers in healthcare that may not be possible with merely manual efforts.…”
Section: Discussionmentioning
confidence: 99%
“…They can involve the derivation of quality indicators and the aggregation of expert opinions as well as various clinical data to obtain compliance scores [37,38]. We did not incorporate such checks into this study, but think that integration of various such metrics would be possible with the same set-up, yielding valuable insights for decision makers in healthcare that may not be possible with merely manual efforts.…”
Section: Discussionmentioning
confidence: 99%
“…A UK study showed that a more flexible effort led by individual physicians to apply evidence‐based guidelines was more effective than organizationally enforced efforts [50]. This would explain the effectiveness of addressing the barriers to physicians using guidelines, through presentations by opinion leaders and by educational outreach [51–54].…”
Section: Discussionmentioning
confidence: 99%
“…To accept that decisions should primarily be based on scientific evidence is to accept that they should not be based on other aspects. However, national and international surveys suggest that compliance with clinical practice guidelines is still only moderate (Hasenbein et al 2006;Albakri et al 2003;Mohammed et al 2005) and that there seems to be no positive correlation between physicians' adherence to guidelines and the underlying strength of evidence (Hasenbein et al 2006;Brand et al 2005). In health care, disagreements frequently occur over thresholds for interventions or whether potential harm exceeds potential benefits.…”
mentioning
confidence: 96%